HARMONY OF SOUND AND SILENCE IN THE UZBEK AND ENGLISH LANGUAGES - Elmirzayeva Maftuna Dusmurodovna; To‘ychiyev Azamat Farxod o‘g‘li (Western European Studies, 2025)
This article explores the complex relationship between phonological features, with a particular focus on intonation and pauses, in shaping the rhythm and melody of spoken language. Intonation, often compared to the musicality of speech, dictates the rise and fall of pitch, adding layers of meaning and emotion to communication. Pauses, in contrast, create moments of silence within the flow of speech, providing opportunities for reflection, emphasis, and anticipation. Through a detailed examination of these elements, the article reveals the dynamic balance between sound and silence in spoken language, emphasizing their role in conveying intention, fostering connection, and enhancing human communication. By recognizing and understanding these subtle aspects, we gain a deeper understanding of the complexities of language and its significant influence on human interaction and comprehension.
Keywords: Intonation; Pause; Phonological features; Spoken language